2020
DOI: 10.1111/ijfs.14770
|View full text |Cite
|
Sign up to set email alerts
|

End‐user preferences for pounded yam and implications for food product profile development

Abstract: The study reports end user preferences for pounded yam in two pounded yam consuming regions (south‐west and south‐east) in Nigeria and its implications for trait evaluation by breeding programme. Key user‐preferred quality traits for pounded yam were colour and textural quality followed by taste and aroma. There were regional differences in ranking of these quality attributes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…For instance, white FC is the most preferred consumer trait in West Africa, while purple color is preferred in French Guyana, the Philippines, and India. 11,40 Several studies have reported significant variations in the nutritional properties of different colored yams. 27,28 Purple yam is enriched in anthocyanins, which are strong antioxidants providing additional nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, white FC is the most preferred consumer trait in West Africa, while purple color is preferred in French Guyana, the Philippines, and India. 11,40 Several studies have reported significant variations in the nutritional properties of different colored yams. 27,28 Purple yam is enriched in anthocyanins, which are strong antioxidants providing additional nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…For boiled yam, mealiness, waxiness, sogginess, stickiness, and hardness are essential textural parameters. Mealiness is the ease of disintegration of the boiled yam, and processors reported it as an indicator of pounded yam quality ( Otegbayo et al., 2021 ). It has been reported in several studies that the textural qualities of boiled yams are important parameters that determine the overall acceptability of farmers, processors, and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The tubers of this crop contain many bioactive compounds, such as mucilage polysaccharides and steroidal sapogenins [24]. Yam polysaccharides are considered im-portant components that provide both biological and physicochemical properties and, thus, can be isolated and used as health-promoting ingredients in foods [25,26]. The yam polysaccharides have also been assessed for their chemical and biological properties, such as immune-modulatory, anti-oxidative, anti-inflammatory, and anti-tumor effects.…”
Section: Introductionmentioning
confidence: 99%